Assessing the Impact of Religious Registration. Issue 4 (9th May 2018) - Finke, Roger; Mataic, Dane R; Fox, Jonathan
Abstract: Religious groups often rely on a registration process to receive the legal status needed to operate openly. Yet, the registration process has become a recent source of controversy. This research uses case studies, trend data from three global collections, and fixed effects models using 19 waves of data to test for the consequences of introducing registration requirements within a nation. The case studies help us to understand the controversies and to identify how registration requirements have been used to increase restrictions on religions in the past, while the trend data document the increasing use of these requirements for discriminating against religions. Finally, the fixed effects models find that introducing registration requirements within a nation was followed by increased religious restrictions, especially for minority religions.